Self-Assessment System, Peran Renjani, dan Modernisasi Administrasi Perpajakan terhadap Kepatuhan SPT - Nahrul Ebim; Siti Ratna Sari Dewi (GLOBAL SCIENTS PUBLISHER, 2026)
This study examines the influence of the Self-Assessment System, the role of Tax Volunteers for the Nation (Renjani), and the modernization of the tax administration system on Annual Tax Return (SPT) filing compliance among individual taxpayers registered at KPP Pratama Kosambi. The study addresses a structural gap in which the compliance ratio appears to rise even though the absolute number of taxpayers who file returns has declined, driven by a shrinking base of taxpayers obligated to report. Using a quantitative associative approach grounded in the Theory of Planned Behavior, primary data were collected from 110 individual taxpayers selected through purposive sampling and analyzed with multiple linear regression in SPSS 27. The results show that the Self-Assessment System and modernization of the tax administration system each have a positive and significant effect on compliance, while the role of Renjani has no significant partial effect. Jointly, the three variables significantly affect compliance, explaining 67.1% of its variation. These findings imply that sustained compliance requires strengthening independent taxpayer awareness, extending volunteer assistance beyond the filing season, and maintaining stable, user-friendly digital tax administration systems.